PENGARUH COGNITIVE BIAS DAN EMOTIONAL BIAS TERHADAP KEPUTUSAN PENEMPATAN DANA UNTUK MODAL KERJA PADA USAHA KECIL MENENGAH (UKM) DI PULAU LOMBOK PADA MASA PANDEMI COVID 19 - Siti Aisyah Hidayati; Sri Wahyulina; Embun Suryani (Master of Management, Mataram University, 2022)
This study aims to analyze the Effect of Cognitive Bias and Emotional Bias on Fund Allocation Decision for Working Capital in Small and Medium Enterprises (SMEs) on Lombok Island during the Covid 19 Pandemic. The theoretical contribution of this research is expected to contribute to science and the development of behavioral finance theory that related to financial decision making and company performance in Small and Medium Enterprises (SMEs). In addition, behavioral finance is also expected to be the subject of financial management courses. Furthermore, the practical contribution of this research is expected to provide input, suggestions and recommendations to the policy makers of the NTB Provincial Government in making policies related to the development of SMEs. This research is a quantitative approach-based research, with the type of explanatory research. The research population is all SMEs located on the island of Lombok. The sampling technique is carried out by non-probability sampling, which uses judgment sampling, namely selecting SMEs that are engaged in the pottery industry and have already exported. From the existing population, there are 34 (thirty four) SMEs that can be taken as samples. Respondents in this study are the owners of each of these SMEs. The data collection technique used in this research is using a questionnaire. To achieve the research objectives and hypothesis testing, the data obtained will be processed according to the needs by using the statistical tool GSCA (Generalized Structured Component Analysis). The results showed that Cognitive Bias and Emotional Bias had a positive and significant impact on fund allocation decision for Working Capital in Small and Medium Enterprises (SMEs) on Lombok Island during the Covid 19 Pandemic. This was motivated by the age of most of the respondents of productive age, mostly male, the education level is mostly high school and college and the length of business is more than 15 (fifteen) years. Keywords: cognitive bias, emotional bias, fund allocation decision for working capital